A Review of High-Temperature and High-Pressure Experimental Apparatus Capable of Generating Differential Stress - Ren, Dongsheng; Li, Heping (Frontiers in Earth Science, 2022)
It has been demonstrated that the matters in the earth’s interior are subjected to isotropic hydrostatic pressure and are also extensively superimposed by the differential stress. The differential stress contributes significantly to the free energy of matters and it is the determining factor controlling the composition, structure, configuration, properties, and interaction processes of the matter system. Hence, the differential stress is one of the most fundamental thermodynamic variables governing the earth’s interior system along with the temperature and the hydrostatic pressure. Nevertheless, due to the limitations of high-temperature and high-pressure (HT-HP) setup and in situ measurement techniques as well as limited understanding of the differential stress, previous HT-HP experiments of the earth’s interior didn’t cover the role of the differential stress except for some special stress-strain mechanics experiments and piezolysis and kinetic metamorphism experiments. This makes many of the knowledge about the earth’s interior obtained from HT-HP experiments generally questionable. Currently, HT-HP experimental apparatus that can be used to simulate the temperature, hydrostatic pressure, and differential stress in the earth’s interior includes the Griggs press, the Paterson rheometer, the D-DIA press, the RDA press, and the torsional diamond anvil cell. The maximum hydrostatic pressure that can be simulated in the Griggs press at high temperatures is only about 2 GPa and there is large uncertainty in the calibration of the differential stress. The Paterson rheometer provides too low confining pressure. The D-DIA press and RDA press can simulate a wide range of temperature and pressure but the D-DIA press can achieve very small strain variables and the RDA press has very heterogeneous sample stresses. The torsional diamond anvil cell can only accept a small sample size and it is difficult to calibrate the differential stress. Also, these existing HT-HP experimental apparatus with the differential stress are not easily interfaced with in situ measurement systems for investigating the physical properties such as electrical, ultrasonic, and thermophysical properties. Hence, scholars need to invest more efforts in the research and development of HT-HP apparatus with the differential stress in the future to properly understand the composition, structure, configuration, properties, and interactions of the matter in the earth’s interior.